Contributors to cancer-related fatigue in childhood cancer survivors and the use of non-pharmacological interventions: a scoping review protocol. (16th September 2021) - Levesque, Ariane; Caru, Maxime; Duval, Michel; Laverdière, Caroline; Sultan, Serge
ABSTRACT: Objective: This scoping review will aim to identify the domains contributing to cancer-related fatigue in childhood cancer survivors and will explore whether non-pharmacological interventions have addressed these domains. This information will help to better define cancer-related fatigue, identify knowledge gaps in the literature, and direct future research efforts. Introduction: Cancer-related fatigue is a commonly reported symptom in aftercare following childhood cancer treatments. However, its operational definition and contributors are unclear, which makes it difficult to select targets and design adequate interventions. In this scoping review, we will identify contributing domains to help clarify their role as key characteristics of cancer-related fatigue. We will then review the evidence as to whether these contributing domains have been addressed by non-pharmacological interventions aimed at fatigue. Inclusion criteria: We will include articles on cancer-related fatigue following childhood cancer treatments (age at diagnosis ≤ 21 years) and non-pharmacological interventions aimed at reducing fatigue. Both will retain qualitative and quantitative studies will be considered for inclusion. Methods: In accordance with the JBI methodological framework for conducting scoping reviews, we will perform a search in PubMed, PsycINFO, CINAHL, Embase, Cochrane Library, Grey Matters, OAlster, and OpenGrey. We will use the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist. Studies published in English or French will be included, with no date limitations. The data collection and analysis of eligible articles will be performed by two independent reviewers and will be classified in summary tables. The findings on contributors to cancer-related fatigue in childhood cancer survivors will be synthesized in a cross table linking contributor domains with intervention type.